Diversity of insect galls associated with Eucalyptus alba & E. urophylla in altitudinal zones in Timor Island, Indonesia - Lindung Tri Puspasari; DAMAYANTI BUCHORI; ROSICHON UBAIDILLAH; HERMANU TRIWIDODO; PURNAMA HIDAYAT (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Puspasari LT, Buchori D, Ubaidillah R, Triwidodo H, Hidayat P. 2021. Diversity of insect galls associated with Eucalyptus alba & E. urophylla in altitudinal zones in Timor Island, Indonesia. Biodiversitas 22: 2667-2679. We investigated the galling insects associated with two species of Eucalyptus, namely E. alba Reinw. and E. urophylla S.T. Blake in different altitudinal zones in Timor Island, Indonesia. This is the first report for Indonesia of the diversity patterns and community structures of galling insects in these two species of eucalyptus and the type of galls they produce. Surveys and data collection were carried out between October 2017 and June 2018 at different altitudes of secondary forest in Timor Tengah Selatan district, Timor. We visited five altitudinal zones (± 829 m asl., ± 942 m asl. ± 1,621 m asl., ± 1992 m asl., and ± 2457 m asl.) and selected 25 eucalyptus plants of 3 to 5 m in height in each altitudinal zone from which to collect insect galls. The galls were observed on leaves, upper leaves (shoots), outer leaves, symptomatic twigs and stems. The galls were taken to the laboratory for rearing of the insects they contained. A total number of 12 gall types were found in E. alba and 15 in E. urophylla from which 28 insect morphospecies were identified belonging to 16 families and five orders. The order Hymenoptera was represented by ten families: Bethylidae, Torymidae, Eulophidae, Eupelmidae Eurytomidae, Pteromalidae, Encyrtidae, Mymaridae, Braconidae and Scelinonidae while the order Diptera was represented by three families: Fergusoninidae, Cecidomyiidae and Chaoboridae. Galling species diversity ranged from 1.71 to 2.38 on the Shannon-Wiener index and 0.75 to 0.87 on the Simpson index and showed that the galling-insect communities were species-rich and composed of galling formers and very few inquilines. In the study, communities are categorized and structured according to different types of galling insects, including those that induce galling, those that are parasitoid, and those that are inquiline. Within the category of gall-forming insects in the two species of eucalyptus, Eulophidae is found to be the dominant family. Our field data makes an important contribution to basic knowledge of insect galling patterns in eucalyptus forests and constitutes baseline data for the implementation of pest control.